2018
DOI: 10.2196/11655
|View full text |Cite
|
Sign up to set email alerts
|

Mining Open Payments Data: Analysis of Industry Payments to Thoracic Surgeons From 2014-2016

Abstract: BackgroundThe financial relationship between physicians and industries has become a hotly debated issue globally. The Physician Payments Sunshine Act of the US Affordable Care Act (2010) promoted transparency of the transactions between industries and physicians by making remuneration data publicly accessible in the Open Payments Program database. Meanwhile, according to the World Health Organization, the majority of all noncommunicable disease deaths were caused by cardiovascular disease.ObjectiveThis study a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…14 In the field of thoracic surgery, less than 2 percent of thoracic Plastic and Reconstructive Surgery • January 2022 surgeons received greater than 52 percent of total industry payments, with seven thoracic surgeons receiving payment amounts in excess of $1 million. 15 The "apical" nature of industry contributions, with relatively few surgeons receiving the vast majority of net industry dollars, does appertain to the field of plastic surgery.…”
Section: Plastic and Reconstructive Surgery • January 2022mentioning
confidence: 99%
“…14 In the field of thoracic surgery, less than 2 percent of thoracic Plastic and Reconstructive Surgery • January 2022 surgeons received greater than 52 percent of total industry payments, with seven thoracic surgeons receiving payment amounts in excess of $1 million. 15 The "apical" nature of industry contributions, with relatively few surgeons receiving the vast majority of net industry dollars, does appertain to the field of plastic surgery.…”
Section: Plastic and Reconstructive Surgery • January 2022mentioning
confidence: 99%
“…For the 3-year follow-up period, the initial data collection period ran from June 20, 2019 to July 1, 2019, and the final data collection period ran from June 20, 2022 to July 1, 2022. A period of 3 years is an acceptable and widely used length for a follow-up period (17)(18)(19); thus, we chose 3 years as the follow-up time for the comparison.…”
Section: Data Sourcesmentioning
confidence: 99%
“…The U.S. legislation has certainly been a boon for researchers examining conflicts of interest (COIs) and prescribing behavior. Dozens of articles using Open Payments data have been published, including national analyses of gift acceptance among physicians, 7,8 and many analyses of payments within multiple specialties, including oncologists, 9 neurologists, 10 cardiologists, 11 thoracic surgeons, 12 and ophthalmologists. 13 Open Payments has enabled numerous studies of discrepancies between disclosures of conflicts of interest and reported payments.…”
Section: What the Sunshine Act Revealedmentioning
confidence: 99%